End‐stage renal disease in a child with focal segmental glomerulosclerosis associated with a homozygous NUP93 variant - Ratna Acharya (Wiley, 2021)
Abstract This report highlights that the genetic causes of FSGS, including NUP93 gene variant, such as the one described in this report, progress to end‐stage renal disease rapidly and that the risk of recurrence post‐renal transplantation is less likely.